2002
DOI: 10.1023/a:1014424723466
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The role of immunosuppressive therapy in the management of IgA nephropathy (IgAN) remains controversial. No consensus has yet emerged on the specific treatment of IgAN and this is mostly related to the lack of complete understanding of the multifactorial pathogenesis of the disease. Choice of appropriate therapeutic agents is further limited by the difficulty in identifying patients who would most likely benefit from therapy. Immunosuppressive therapy has not been recommended in patients with isolated hematuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Treatment with prednisone appeared beneficial in reversing proliferative lesions as much as possible and prevented the development of fibrosis. Such treatment has been shown to affect prognosis [11, 27, 28]. While in this non-randomized trial prednisone therapy was more often used in the progressive group than in the non-progressive group (8 of 10 patients in the progressive group, 27 of 41 patients in the non-progressive group, p < 0.05), our results showed that prednisone therapy is a risk factor for renal insufficiency.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Treatment with prednisone appeared beneficial in reversing proliferative lesions as much as possible and prevented the development of fibrosis. Such treatment has been shown to affect prognosis [11, 27, 28]. While in this non-randomized trial prednisone therapy was more often used in the progressive group than in the non-progressive group (8 of 10 patients in the progressive group, 27 of 41 patients in the non-progressive group, p < 0.05), our results showed that prednisone therapy is a risk factor for renal insufficiency.…”
Section: Discussioncontrasting
confidence: 51%
“…These patients presented with azotemia that represented long-standing disease that differs from the classic presentations, either because the patients did not come to early medical attention or because the patients were referred late with an established diagnosis. Once renal function impairment develops, ESRD appears inevitable [11]. In addition, we also found relatively severe pathologic types in a number of cases, such as FSGS and MPGN, implying a clinicopathological disassociation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Expert opinions in children advocate a cut-off of 0.5 g/d per 1.73 m 2 for partial remission, and 0.16 g/d per 1.73 m 2 for complete remission; these thresholds have been used in RCTs. 478, 483 …”
Section: Rationalementioning
confidence: 99%
“…Treatment with glucocorticoids alone or combined therapy with glucocorticoids and other immunosuppressive agents have shown beneficial effects by reducing proteinuria and improving renal function (7,8). According to the guidelines ‘Kidney Disease: Improving Global Outcomes’ (KDIGO) (9), which are based on the results of previous studies (7,10,11), patients with persistent proteinuria of >1 g/day following 6 months of treatment with renin-angiotensin system (RAS) inhibitors are suggested to receive a 6-month course of corticosteroid therapy.…”
Section: Introductionmentioning
confidence: 99%